The asymmetrically segregating lncRNA cherub is required for transforming stem cells into malignant cells - Landskron, Lisa (eLife, 2018)
Tumor cells display features that are not found in healthy cells. How they become immortal and how their specific features can be exploited to combat tumorigenesis are key questions in tumor biology. Here we describe the long non-coding RNA cherub that is critically required for the development of brain tumors in Drosophila but is dispensable for normal development. In mitotic Drosophila neural stem cells, cherub localizes to the cell periphery and segregates into the differentiating daughter cell. During tumorigenesis, de-differentiation of cherub-high cells leads to the formation of tumorigenic stem cells that accumulate abnormally high cherub levels. We show that cherub establishes a molecular link between the RNA-binding proteins Staufen and Syncrip. As Syncrip is part of the molecular machinery specifying temporal identity in neural stem cells, we propose that tumor cells proliferate indefinitely, because cherub accumulation no longer allows them to complete their temporal neurogenesis program.